In Cahoots with Neo-Indigenism - Brian D. Haley (Genealogy, 2024)
Academia’s support for neo-indigenes is a significant component of their professional success. I describe how this support operates, drawing a model of cahooting from Edward Dolnick’s analysis of art forgery in The Forger’s Spell. Cahooting reflects the importance of social relationships to the construction of perceived truth and virtue. It corrupts academia at multiple levels through these relationships, undermining the pursuit of truth and goals of equity and inclusion.